JURIDICAL ANALYSIS OF CHILD AND HUMAN RIGHTS TEACHER PROFESSIONALISM - Marzuki (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research is a study to analyze the protection of children in schools and the protection of teacher professionalism, especially to maintain a balance between protecting children's human rights in schools with the implementation of teacher professionalism which also needs to be protected in educating children. The specification or type of research in this study is descriptive in nature, using normative juridical research methods through several approaches: the statutory approach and the conceptual approach. The results showed that based on data from the Indonesian Child Protection Commission (KPAI) in the first semester of January to July 2022, 12 cases were recorded, consisting of 3 cases occurring in schools in areas under the auspices of the Ministry of Education and Culture with a percentage of 25%. Meanwhile, cases in the education unit under the auspices of the Indonesian Ministry of Religion were 9 cases or 75%. Based on education level, 2 (16.67%) cases of violence occurred at the Elementary School (SD) level. Middle school level was 1 (8.33%) case. Islamic boarding schools 5 (41.67%) cases. Madrasas are places of recitation/place of worship in 3 (25%) cases, and 1 (8.33%) place for music courses for kindergarten and elementary school aged children. The age range of the victims was between 5-17 years. Victims numbered 52 children with details of 16 (31%) boys and 36 (69%) girls. While the perpetrators totaled 15 people consisting of: 12 teachers (80%), 1 (6.67%) owner of the boarding school, 1 (6.67%) child of the owner of the boarding school, and 1 (6.67%) senior of the victim. On the other hand, violence against teachers is still common, for example, in August 2016 there was a beating of a father and son against a teacher at a well-known school in Makassar. This case felt very strange because according to the news, the child, who incidentally was a student of the battered teacher, also took the opportunity to throw punches at the time his father was "crazy" at school. In early February 2018, it was also reported that Achmad Budi Cahyanto, a teacher at SMAN 1 Torjun, Sampang, Madura, died after being beaten by a student named HZF. Therefore, the existence of Law no. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection, is intended to prevent arbitrary actions against Indonesian children, as well as Law no. 14 of 2005 concerning Teachers and Lecturers,